2014
DOI: 10.1107/s2053230x14009649
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray characterization of the 2,4′-dihydroxyacetophenone dioxygenase fromAlcaligenessp. 4HAP

Abstract: The enzyme 2,4'-dihydroxyacetophenone dioxygenase (or DAD) catalyses the conversion of 2,4'-dihydroxyacetophenone to 4-hydroxybenzoic acid and formic acid with the incorporation of molecular oxygen. Whilst the vast majority of dioxygenases cleave within the aromatic ring of the substrate, DAD is very unusual in that it is involved in C-C bond cleavage in a substituent of the aromatic ring. There is evidence that the enzyme is a homotetramer of 20.3 kDa subunits each containing nonhaem iron and its sequence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Data-processing statistics are shown in Table 1, where it can be seen that the traditional R merge is slightly high at 13.6% and the outer shell completeness is slightly low, but that the data are of excellent consistency to 2.2 Å resolution according to the half-set correlation criterion of Karplus & Diederichs (2012). A more comprehensive account of the expression, purification, crystallization and data collection is given in Beaven et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-processing statistics are shown in Table 1, where it can be seen that the traditional R merge is slightly high at 13.6% and the outer shell completeness is slightly low, but that the data are of excellent consistency to 2.2 Å resolution according to the half-set correlation criterion of Karplus & Diederichs (2012). A more comprehensive account of the expression, purification, crystallization and data collection is given in Beaven et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Crystals of Alcaligenes sp. 4HAP DAD which diffracted synchrotron radiation to 2.2 Å resolution were obtained by in situ chymotrypsinolysis (Beaven et al, 2014). They belonged to space group P6 5 22 with one molecule per asymmetric unit and allowed the structure to be solved and refined to an R factor of 17.3% and an R free of 21.8%.…”
Section: Crystallographic Datamentioning
confidence: 99%
“…Use of the MATT-PROB server (Kantardjieff & Rupp, 2003) indicated that there were likely to be two molecules of DAD (which are approximately 20 kDa each) in the asymmetric unit. However, attempts at molecular replacement with various search models which had sequence homology to DAD failed to yield a solution, and when the structure of DAD was solved in a different crystal form (Beaven et al, 2014;Keegan et al, 2014) this also did not provide a convincing solution with the 1.1 Å resolution data set.…”
Section: Data Processingmentioning
confidence: 99%
“…4HAP has been shown to be a homotetramer in which each subunit has a molecular mass of 20.3 kDa and consists of 177 amino acids (Hopper & Kaderbhai, 1999). Recently, structural studies have shown that it is a member of the cupin superfamily, which is characterized by a conserved -barrel fold (Beaven et al, 2014;Keegan et al, 2014). The core cupin fold of DAD is formed by residues 60-132, which assemble into two four-stranded antiparallel -sheets, forming a double-stranded -helix that is extended at one end by an additional -hairpin in each sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The putative binding site for the aromatic substrate is buried and is mainly composed of conserved hydrophobic residues. The two -hairpins forming one end of the barrel are somewhat splayed apart, exposing an unusual hydrophobic patch which might be the entry point for substrate (Beaven et al, 2014;Keegan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%